2014
DOI: 10.1007/s11105-014-0819-9
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression

Abstract: Transposable elements (TEs) are major components of eukaryotic genomes and have played important roles in genome evolution. Plant introgressive hybridization is widespread in nature and may induce a wide range of genetic and epigenetic variations including reactivation of dormant TEs. Newly elicited TE transpositions may lead to heritable expression alteration in genes adjacent to excision and insertion sites and consequently to phenotypic novelty. Prior studies showed that distant hybridization between sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Horizontal gene transfer regularly acts as a genetic bridge between vastly diverged species [ 257 , 258 ]. Horizontal transfers of TEs between angiosperm genomes have been documented in nature [ 263 , 264 , 265 ] and experimentally [ 266 ]. In Drosophila , HGT seems to have occurred from the willistoni species group to D. melanogaster .…”
Section: Introgression and Transposable Elementsmentioning
confidence: 99%
“…Horizontal gene transfer regularly acts as a genetic bridge between vastly diverged species [ 257 , 258 ]. Horizontal transfers of TEs between angiosperm genomes have been documented in nature [ 263 , 264 , 265 ] and experimentally [ 266 ]. In Drosophila , HGT seems to have occurred from the willistoni species group to D. melanogaster .…”
Section: Introgression and Transposable Elementsmentioning
confidence: 99%
“…However, in a later work performed with the same material [32] it is stated with absolute certainty that the introgression lines originated from the incongruent crossing of two types of rice arose exclusively under the influence of pollen that did not incorporate DNA into the genome of the lines. In this study, the activation of transposons was confirmed.…”
Section: Facts Of the Variability Of The Recipient Genome Of Hybrid O...mentioning
confidence: 94%
“…Numerous studies on the expression of alien genes against the background of the resident genome have shown that a change in the expression of such a gene is quite common and is a consequence of the interaction between the alien gene and the genetic environment of the host genome [32,[37][38][39][40]. For wheat, the attenuation of resistance was repeatedly shown when a resistance gene was transferred from an alien species to the background of the wheat genome [9,[40][41][42][43]45].…”
Section: Attenuation Of Alien Gene Expressionmentioning
confidence: 99%
“…For example, TE excision or insertion resulted in heritable altered expression of eight neighbouring genes in X9 rice line with four being significantly induced and four suppressed. Particularly, three of the induced genes were found within QTLs related to 1000 seed weight and grain length (Wu et al, 2015).…”
Section: Summary Of Gene Distribution In Qshb 9-2mentioning
confidence: 99%